Implementasi Metode Reward dalam Mengembangkan Kedisiplinan Anak Kelompok B di TK Az-Zahrah - Safitri, Mufarrohatus; Dwi Anggraini, Denok (UIR PRESS, 2025)
This research is motivated by the large number of educators who still do not understand child development and methods that are appropriate to child development and there are still many who show an undisciplined attitude. The aim of this research is to determine the implementation of the reward method in developing children's discipline at Az-Zahrah Kindergarten. This research uses a descriptive qualitative approach. The data sources in this research are school principals and teachers. The results of the research show that (1) The implementation of the reward method at Az-Zahrah Kindergarten uses several forms including praise, grades/awards and prizes as a form of appreciation for students which is supported by suggestions from student guardians as well as funding from the school which is carried out on an ongoing basis. (2) to develop discipline at Az-Zahrah Kindergarten using the reward method as a form of appreciation for students so that teachers can easily direct them to follow the learning flow that has been designed to be interesting by the teacher. (3) supporting factors for implementing the reward method, namely support and advice from the school, parents and positive responses from students, then inhibiting factors, namely lack of awareness from students and differences in students' characters in showing their behavior. The conclusion in this research shows that the implementation of the reward method at Az-Zahrah Kindergarten is going well according to the use of praise, appreciation and prizes so that children are able to be disciplined in participating in learning activities designed by the teacher.